2008
DOI: 10.1074/jbc.m800889200
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved Mechanism of Extracellular Gate Opening and Substrate Binding in a Glutamate Transporter

Abstract: Glutamate transporters, also referred to as excitatory amino acid transporters (EAATs), are membrane proteins that regulate glutamatergic signal transmission by clearing excess glutamate after its release at synapses. A structure-based understanding of their molecular mechanisms of function has been elusive until the recent determination of the x-ray structure of an archaeal transporter, Glt Ph . Glt Ph exists as a trimer, with each subunit containing a core region that mediates substrate translocation. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
122
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(142 citation statements)
references
References 53 publications
20
122
0
Order By: Relevance
“…These observations suggest an inter-subunit coupling that restricts simultaneous opening of subunits. This coupling is reminiscent of the observations made for GltPh simulations in the OF state, 42 which were attributed to intersubunit steric effects restraining the simultaneous opening of all three HP2 gates. The ability of the transport cores of the individual subunits to come into close proximity was confirmed experimentally for the OF state of GltPh.…”
Section: No Simultaneous Opening Of Two or More Subunits Is Observed mentioning
confidence: 80%
See 2 more Smart Citations
“…These observations suggest an inter-subunit coupling that restricts simultaneous opening of subunits. This coupling is reminiscent of the observations made for GltPh simulations in the OF state, 42 which were attributed to intersubunit steric effects restraining the simultaneous opening of all three HP2 gates. The ability of the transport cores of the individual subunits to come into close proximity was confirmed experimentally for the OF state of GltPh.…”
Section: No Simultaneous Opening Of Two or More Subunits Is Observed mentioning
confidence: 80%
“…Even though various conformations of GltPh have been resolved to date, 15,[34][35][36] and several simulations have been performed using these structural data, 11,[37][38][39][40][41][42][43] the mechanism of function of aspartate transporters (and their mammalian glutamate orthologs) is not yet well-understood. GltPh is a homotrimer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T370 was not predicted to form part of this Na + -binding site (21). Shrivastava et al (20) noted that T370 (T314 in Glt Ph ) is able to bind water and that this water, in combination with the bound glutamate, could participate in coordinating a Na + ion. Taken together, both thermodynamic and steric considerations point toward the potential location of an ion-binding site in this region, in good agreement with our results from GCMC/MD modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier theoretical studies also have suggested that the third Na + ion binds in proximity to the bound amino acid substrate (20,21). Holley and Kavanaugh (21), using the knowledge-based method VALE, identified a putative third ion-binding site in which a Na + ion was coordinated by the bound amino acid substrate and three backbone oxygen atoms from HP2.…”
Section: Discussionmentioning
confidence: 99%